(untitled) (INNOVATIVE ECONOMY, 2020)
Pariy O.M. ORGANIZATIONAL CULTURE AS AN IMPORTANT COMPONENT OF THE ENTERPRISE MANAGEMENT SYSTEM Purpose. The aim of the article is to research theoretical positions and development of practical recommendations for the formation of the concept of organizational culture as part of the modern enterprise management paradigm. The purpose of this publication is to substantiate the role of organizational culture in ensuring the effective management of the enterprise Private Joint-Stock Company “New Kramatorsk machine-building plant”. Methodology of research. We use general scientific and specific methods, methodological techniques and research tools in order to achieve this goal and to solve the above-mentioned problems in our intelligence, in particular: analysis and synthesis (interpretation of the economic essence of the categories “organizational culture”, “corporate culture”, description of the main stages of organizing the culture in composition of the modern enterprise management paradigm); the method of causal relationship (identification of factors of influence on organizational culture); the method of empirical research. Findings. The factors influencing the development of organizational culture are determined, as well as a set of indicators of corporate culture quality of the enterprise is described. The factors of development of organizational culture of the enterprise and its influence on the development of scientific and technical creativity of the employees, as well as on business activity of the enterprise are presented. The necessity of information provision and communications at the enterprise for the development of the corresponding organizational culture is substantiated. It is proved that the concept of organizational culture acts as a necessary and systemically generating factor for all components of the management paradigm. Originality. The scientific novelty of the research results is to deepen theoretical and methodological positions and to substantiate practical recommendations regarding the formation of the concept of organizational culture as part of the modern paradigm of enterprise management. Practical value. The practical significance of the research results is to use theoretical and practical recommendations when implementing the concept of organizational culture as an important lever of enterprise management. Key words: organizational culture; organizational values; modern paradigm of management; strategic management; information provision; enterprise.